Tesi per una filosofia della tecnica - Mazzarella, Eugenio (Mechane, 2020)
By the term metaphysics we mean the emerging of human transcendence in cosmos: a transcendence that wide open in a double position: on the one hand, the poietic complex of social and manufactural praxis (techne), thanks to which the Anthropos held himself in the world that he has revealed, structuring his own transcendence; on the other, the ecstatic entrust (religio) to the world – both natural and historical – in which he is open and from which is ruled since his deepest constitutive fibre. In this article we will try to show that the very ambition of technology is to subsume in itself the religious stance, preparing for human Dasein the foundation of sense of his being in the world, given to him by religion so far.